Comparing the antecedents of green computer behavior at acquisition, use, and disposal consumption stages from the moral norm and consumer attributes perspectives - Eu-Gene Siew; Paul H.P. Yeow; Yuen Yee Yen; Wee Hong Loo (PLoS ONE, 2025)
Computers can have an adverse effect on the environment throughout the consumption stages of their acquisition, use, and disposal. Previous studies have predominantly focused on specific stages of consumption, leading to limited research on the utilization of the values-belief-norm (VBN) model in conjunction with consumer attributes like environmental knowledge, habits, and self-identity to forecast green computer behavior across all three stages of consumption. Consequently, the aim of this research is to identify and compare the VBN factors and consumer attributes that influence green computer behavior during the three consumption stages. An understanding of the differences in the antecedents at each stage can help in the development of a holistic pro-environmental intervention to mitigate the harmful environmental effects of computer consumption. An analysis of the data collected from survey questionnaires administered to Malaysian computer consumers reveals that different factors are prominent at each stage of consumption. Self-identity is only important during computer acquisition, while habits are only important during computer use. Although environmental knowledge and VBN factors are significant at all phases, the effects differ at each stage. Environmental knowledge is the most important factor at the acquisition stage. As for the VBN factors, the ascription of responsibility is the most important factor at the acquisition stage, while the ascription of responsibility and awareness of consequences are the most important factors at the use stage. Personal norms are the most important factor at the computer disposal stage and are the most important predictor of computer disposal behavior. The outcomes of this research can help manufacturers, marketers, government policymakers, and academics engage with consumers to promote green computer behavior. The novelty of this research is in comparison of the antecedents of consumer green computer behavior at each stage of consumption.